SHR-8068 combined with adebrelimab and bevacizumab in the treatment of refractory advanced colorectal cancer: study protocol for a single-arm, phase Ib/II study - Zhang, Pei; Li, Xiaofen; Wang, Xin; Yang, Yu; Wang, Jianfei; Cao, Dan (Frontiers in Immunology, 2024)
The third-line treatment for refractory colorectal cancer (CRC) has limited efficacy. This study aimed to evaluate the safety and efficacy of SHR-8068 (an anti-CTLA-4 antibody), combined with adebrelimab (an anti-PD-L1 antibody), and bevacizumab in refractory non-microsatellite instability-high (MSI-H) or proficient mismatch repair (pMMR) CRC.This study is a prospective, open-label, single-center phase Ib/II clinical trial. Patients with pathologically confirmed pMMR/ non-MSI-H metastatic colorectal adenocarcinoma who have failed ≥ 2 lines prior standard systemic treatments will be enrolled (n=36). The Ib phase will evaluate two dosing regimens of SHR-8068 in combination therapy (n=9 each dosage): SHR-8068 (1 mg per kilogram, every six weeks, intravenously) or SHR-8068 (4 mg per kilogram, every twelve weeks, intravenously) combined with adebrelimab (1200 mg, every three weeks, intravenously) and bevacizumab (7.5 mg per kilogram, every three weeks, intravenously). The efficacy and adverse events (AEs) of these regimens will be assessed to determine the recommended phase II dose (RP2D) of SHR-8068. Those of RP2D group from the phase Ib will be included in the phase II. The study will go to include 18 additional patients according to the one-sample log-rank test design in the phase II. The primary endpoint of the Ib phase is safety, with secondary endpoints including the objective response rate (ORR), progression-free survival (PFS), overall survival (OS), disease control rate (DCR), and quality of life (QOL). The primary endpoint for phase II was PFS, with secondary endpoints including ORR, OS, DCR, safety, and QOL. Identifying biomarkers to predict the efficacy of this regimen is the exploratory study endpoint.This proof-of-concept study would provide safety and efficacy signals of this novel combination treatment for the MSS CRCs in the late-line setting. And it may offer new insights on the clinical application of dual immunotherapy combined with anti-angiogenic therapy in the MSS CRC.This study was registered at ClinicalTrials.gov (NCT06373133).